Children as Collective Goods and Divorce Settlements - Weiss, Yoram; Willis, Robert J. (Journal of Labor Economics, 1985)
The failure of many divorced fathers to comply with court-mandated child support awards has been identified as a major reason why a growing number of children live in poverty in female-headed households. This paper presents a model that seeks to explain why so many divorced fathers allow their children's welfare to suffer as a consequence of divorce. The point of departure is the recognition that children are collective consumption goods from the point of view of the father and mother. Within marriage, proximity and altruism serve to overcome the "free-rider" problem associated with the provision of public goods. However, on divorce the noncustodial parent suffers a loss of control over the allocative decisions of the custodial parent and it is not feasible for the couple to achieve a Pareto-optimal allocation of their joint resources. A model of optimal marriage contracts is constructed in which a couple decides on the allocation of resources within marriage and on the terms of a settlement in the event of divorce. The settlement consists of the determination of custody and transfer of income to the custodial parent. Divorce is endogenous in our model and its occurrence depends on a random variable introduced into the family budget constraint that measures the quality of the marriage match. The analysis yields several useful insights. In addition to explaining the apparently insufficient support by custodians we explain why custody rights and alimony transfers often go in the same direction, most commonly to the wife, and why uneven distribution of income between the spouses increases the probability of divorce.